PERBEDAAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK KELAS XI IPA YANG DIBELAJARKAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN INKUIRI TERBIMBING DI SMA NEGERI 1 MAJENE PADA MATERI POKOK SISTEM KOLOID - Asnia Asnia (Chemistry Education Review (CER), 2017)
The research was quasi-experiment research which aimed to discover whether there were differences of motivation improvement and learning result between the students who taught by problem based leaning model and guided inquiry in SMAN l Majene. The research was conducted in SMAN 1 Majene. The population of the research was the students of class XI IPA of the second semester of academic year 2014/201 5, which consisted of 4 classes. The sample was obtained by employing simple random sampling technique. The instruments used to discover the motivation and learning result were questionnaire and learning result test given at the beginning and at the end of learning. The data analysis consisted of descriptive statistics analysis to describe motivation and learning result and inferential statistics analysis to test the research hypothesis by using t-test. The results of the research showed that: (1) the improvement of learning motivation of the students who taught by using problem based learning model and guided inquiry were both in high category which shown 0.78 and 0.82, (2) the improvement of learning result of the students who taught by using problem based learning model and guided inquiry were both in high category which shown 0.72 and 0.74, (3) first hypothesis test gained the score of p-value 0.095 > 0.05, (4) second hypothesis test gained the score of p-value 0.545 > 0.05. In descriptive statistics analysis, there were differences of improvement of motivation and learning result of the students who taught by using problem based learning model and guided ìnquiry. While in inferential statistics analysis showed that there was no significant difference of motivation and learning result of the students who taught by using problem based feaming model and guided inquiry.